Pelatihan Bahasa Prancis bagi Aktor Pariwisata Desa dan Hospitality Pengusaha Warung Makan Mahasiswa di Masa Pandemi - Baskoro, B. R. Suryo; Subiyantoro, Subiyantoro; Shahab, Ali (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2021)
During the Covid-19 pandemic, almost all economic sectors economy were affected, included the tourism sector (area of hospitality). Welcoming a new stage of normality, the sector needs to prepare. Therefore, French Literature Program FIB provides a basic French language learning to tourism players in Ponggok village, Klaten and health awareness during the pandemy in Kuningan village, Sleman. Since business was being halted at the time, the training program was carried out with team visits to the site and the provision of basic French language training materials and modules in Ponggok village and online discussions on health awareness during the pandemy with food stall owners and students in Kuningan village. The tourism players in Ponggok village seem enthusiastic about receiving French language materials and modules and in the near future the team will come to the site to monitor its development. Meanwhile, stall owners and students in Kinanti realize that this pandemic can only be faced together by maintaining each other’s health protocols. ===== Pada masa pandemi Covid-19, hampir semua sektor ekonomi terkena dampaknya, tak terkecuali sektor pariwisata (bidang hospitality). Menyambut tahap kenormalan baru, sektor tersebut perlu mempersiapkan diri. Untuk itu Prodi Sastra Prancis FIB memberikan pelatihan bahasa Prancis kepada para pelaku pariwisata di desa Ponggok, Klaten dan pembekalan menghadapi new normal di kampung Kuningan, Sleman. Berhubung bisnis sedang dihentikan saat itu, program pelatihan dilaksanakan dengan kunjungan tim ke lokasi dan pemberian bahan dan modul pelatihan bahasa Prancis dasar di desa Ponggok dan diskusi daring untuk pembekalan menghadapi pandemi dengan para pemilik warung makan dan mahasiswa di kampung Kuningan. Para pelaku pariwisata di desa Ponggok tampak antusias menerima bahan dan modul bahasa Prancis dan dalam waktu dekat tim akan datang ke lokasi untuk memantau perkembangannya. Sementara itu, para pemilik warung dan mahasiswa di Kinanti menyadari bahwa pandemi ini hanya dapat dihadapi bersama-sama dengan saling menjaga protokol kesehatan.